Pengaruh Digitalisasi Layanan dan Promosi Agen Brilink Terhadap Inklusi Keuangan Melalui Perubahan Pola Transaksi Masyarakat Sebagai Variabel Intervening di Agen Brilink Desa Cijalingan - Nurazizah, Rida; Tanjung, Hendra; Nurmilah, Risma (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
Financial inclusion is a key pillar in achieving sustainable economic development, particularly in rural areas that still face limited access to formal financial services. In this context, the digitalization of services and promotional activities carried out by BRILink agents serve as strategic efforts to improve community financial inclusion. This study aims to examine the effect of service digitalization and BRILink agent promotion on financial inclusion, both directly and indirectly through the mediating variable of changes in community transaction patterns. The research method employs a quantitative approach with an associative design. Primary data were collected through questionnaires distributed to 100 respondents who are users of BRILink services in Cijalingan Village, Sukabumi Regency. Data analysis was conducted using the Structural Equation Modeling (SEM) method with SmartPLS version 4.0 software. The results indicate that both service digitalization and BRILink agent promotion have a positive and significant effect on changes in community transaction patterns. Furthermore, digitalization, promotion, and changes in transaction patterns significantly influence financial inclusion. These findings suggest that greater utilization of digital technology and effective promotional strategies by BRILink agents encourage a shift in transaction behavior, ultimately leading to improved financial inclusion. The change in transaction patterns also partially mediates the relationship between digitalization, promotion, and financial inclusion, with the overall model explaining 63.8% of the variance in financial inclusion.